A strategy to accelerate the bioleaching of chalcopyrite through the goethite process - Mining, Metallurgy & Exploration (2018) - H. Zhao; R. Liao; W. Qin (Society for Mining, Metallurgy & Exploration)
Theoretically, controlling redox potential to a relatively low value and inhibiting jarosite formation on the chalcopyrite surface would be an effective strategy to accelerate the bioleaching of chalcopyrite. In this work, using limonite as seed crystals, the effects of the goethite precipitation process on the bioleaching of chalcopyrite were studied for the first time. The bioleaching results showed that the addition of limonite controlled the redox potential in an appropriate range and promoted chalcopyrite dissolution through the removal of ferric (Fe3+) ions. X-ray diffraction and scanning electron microscope analyses indicate that limonite significantly induced the goethite precipitation process and inhibited the production of jarosite. We conclude that promoting the goethite precipitation process with limonite is an effective strategy in accelerating the bioleaching process of chalcopyrite.